BUSINESS PROCESS MANAGEMENT IN CZECH HIGHER EDUCATION - Hrabal, Martin; Opletalova, Michaela; Tuček, David (Journal of Applied Engineering Science, 2016)
Business Process Management, both as a managerial discipline and its supportive information and communication technology, is becoming a concern for many business practitioners and research workers. As organizations develop their processes via modelling, simulation, implementation and continuous improvement, they may demand suitable workforce to secure these initiatives such as process owners, business analysts, process analysts etc. This fact puts demands on higher education institutions to provide these competencies and teach their students. Moreover, to provide quality education and research, universities themselves may utilize benefits of Business Process Management. The main goal of this paper is thus to explore the current state of Business Process Management utilization among Czech higher education institutions. Its purpose is to answer the research questions of how do universities in the Czech Republic apply process approach and what process maturity do they achieve? The second concerns of this paper are process owners and their role in process initiatives of Czech universities.